Engaging students is co-creation the answer? - Kéri Anita (The Challenges of Analyzing Social and Economic Processes in the 21st Century, 2020)
Consumer satisfaction has long been a question of great interest in a wide range of fields. Existing research recognizes the critical role played by student satisfaction in higher education. It has been noted that students have changing and variable needs. A considerable amount of literature has been published on the fact that higher education institutions have to react promptly and satisfy students’ needs in order to keep their students and rankings. As student satisfaction is highly dependent on teaching quality, it is essential for higher education institutions to implement new teaching methodologies. Therefore, the aim of this paper is to analyze the concept of a teaching methodology, namely co-creation, and to examine its applicability in the field of economics. With the methodology of co-creation, teachers are able to involve students into the creation of curriculum, which might enhance student involvement and increase student satisfaction.